Studi Kasus : Rendahnya Motivasi Belajar Pada Siswa Latar Layanan Pendidikan Di Sekolah Menengah Atas X - Komang Agung Candra Dinata; Amanda Pasca Rini (CV. ITTC INDONESIA, 2026)
This study aims to examine and address the issue of low learning motivation in a 17-year-old high school student, initialized as RV, at SMA X Surabaya, which underlay various problematic behaviors at school. Through a clinical case study approach, a series of assessments were conducted utilizing observation, interviews, and psychological testing tools (IST, EPPS, SSCT, and projective Graphic tests). The assessment results indicated that the subject experienced a severe decline in intrinsic motivation rooted in family disharmony due to parental divorce, deep-seated feelings of inferiority, and social adjustment barriers. Based on this diagnosis, a psychological intervention was designed, combining individual humanistic counseling with self-disclosure, confrontation, and motivational interviewing techniques, supplemented by a psychoeducation program based on Self-Determination Theory. The intervention was implemented across six in-person sessions at school. Post-intervention evaluation revealed an increase in self-awareness, a shift in learning mindset from external coercion to internal fulfillment, and the emergence of concrete commitments to improve school attendance, task adherence, and interpersonal relations with the mother and peers.